Memory for Spatial Locations in a Patient with Near Space Neglect and Optic Ataxia: Involvement of the Occipitotemporal Stream - Chieffi, Sergio; Messina, Giovanni; Messina, Antonietta; Villano, Ines; Monda, Vincenzo; Ambra, Ferdinando Ivano; Garofalo, Elisabetta; Romano, Felice; Mollica, Maria Pina; Monda, Marcellino; Iavarone, Alessandro (Frontiers in Neurology, 2017)
We studied attention orienting and reaching to remembered spatial locations in a patient (G.P.) with optic ataxia due to bilateral damage to the occipitoparietal areas. G.P. and healthy controls took part in three experiments. In the experiment 1, the participants performed a line bisection task with their right or left hand. The lines were oriented along radial, vertical and horizontal axes. G.P. bisected radial lines farther and vertical lines more above than the controls, consistent with near/lower space neglect and attentional bias toward the far/upper space. The experiment 2 consisted of two tasks: (1) an immediate reaching task, in which G.P. reached target locations under visual control; (2) a delayed visual reaching task, in which G.P. and healthy controls were asked to reach remembered target locations visually presented. Reaching was performed with the right or left hand; both G.P. and healthy controls could foveate target locations. We measured constant and variable distance and direction errors. In immediate reaching task, G.P. accurately reached target locations. In delayed reaching task, G.P. and the healthy participants exhibited an opposite patterns of constant distance errors: G.P. overshot remembered target locations, whereas the controls undershot them. Furthermore, variable errors were greater in G.P. than in the controls. In the experiment 3, G.P. and healthy controls performed a delayed proprioceptive reaching task. In it, participants were asked to reach with their right or left hand remembered target locations proprioceptively presented. Constant errors of G.P. did not differ from those of the controls, whereas variable direction errors were greater in G.P. than in the controls. We suggest that the occipitoparietal damage, and the relatively intact occipitotemporal region, produced in G.P. an attentional orienting bias toward the far/upper space (experiment 1). In turns, the attentional bias selectively shifted forward remembered visual (experiment 2), but not proprioceptive (experiment 3), target locations to-be-reached. Furthermore, the observation that in both delayed reaching tasks the variable errors were greater in G.P. than in the controls suggests that it is possible to detect in optic ataxia not only a visuo- but also a proprioceptivo-motor integration deficit.